-7(t-9)+2t=-8+t

Simple and best practice solution for -7(t-9)+2t=-8+t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(t-9)+2t=-8+t equation:


Simplifying
-7(t + -9) + 2t = -8 + t

Reorder the terms:
-7(-9 + t) + 2t = -8 + t
(-9 * -7 + t * -7) + 2t = -8 + t
(63 + -7t) + 2t = -8 + t

Combine like terms: -7t + 2t = -5t
63 + -5t = -8 + t

Solving
63 + -5t = -8 + t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-1t' to each side of the equation.
63 + -5t + -1t = -8 + t + -1t

Combine like terms: -5t + -1t = -6t
63 + -6t = -8 + t + -1t

Combine like terms: t + -1t = 0
63 + -6t = -8 + 0
63 + -6t = -8

Add '-63' to each side of the equation.
63 + -63 + -6t = -8 + -63

Combine like terms: 63 + -63 = 0
0 + -6t = -8 + -63
-6t = -8 + -63

Combine like terms: -8 + -63 = -71
-6t = -71

Divide each side by '-6'.
t = 11.83333333

Simplifying
t = 11.83333333

See similar equations:

| 27-m=8 | | 2x/4-1/4=x/3-7/3 | | 4a-11=9+3a | | 5(-6+1)-4n=-5+2n | | 24=-3(t+-24) | | 2(n-52)-22=2 | | 2(t-64)=56 | | 67-z=40 | | 2(s+1)=10 | | 4(s-90)=-50 | | (5x-6)(x^2-4x-1)= | | (4x^2)-47+70=0 | | M-52=27 | | 3(v+2)=12 | | 3(b+1)+1=10 | | 3(z+-15)=-60 | | 25-w=46 | | 16=-2(n+-17) | | m^2-n^2-am-an=0 | | 6-2x=-20 | | 15p+19.96=-14.08+11.3p | | 2(3r-7)-(2+r)= | | -11.4u-3.54+19.2u=8.34+8.9u | | -5.6k-16.61=-4.5k | | -13.03+5.1m=12.3m+10.01 | | -12.2w+16.74=-13.6w-7.2 | | 11.5d=-7.56+10.3d | | -6.5u+18.93=1.18-12.8u-8.08 | | -8.53-5+19.5z=18.1z-19.97 | | 7.82-1.5g=11.8g-16.12 | | -8.53-5+19.5z=18.1-19.97 | | -5s+16+12=-17-10s |

Equations solver categories